PENGARUH KOMUNIKASI INTERPERSONAL TERHADAP MINAT BELAJAR SISWA SMP DARUNNAJAH WULUHAN JEMBER - Istianah, Siti Lutfiatul; Swastinah, Titin (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2019)
This study about the effect of interpersonal communication on student interest in learning at SMP Darunnajah Wuluhan Jember with 31 students as respondents. The method used in this research is observation and questionnaire methods. Data analysis using the correlation coefficient formula, by looking for r product moment. Based on the research results, the results obtained a value of 0.410. After being compared with the data analysis table r, the results of the total sample size of the research as many as 31 students of class VII and VIII SMP Darunnajah Wuluhan Jember are greater than the acceptance price at the 5% significant level, namely 0.355 so that the null hypothesis (Ho) is rejected and the hypothesis (Ha) is accepted which means that there is an influence of interpersonal communication on student interest in learning at SMP Darunnajah Wuluhan Jember. Keywords: Interpersonal Communication, Interest in Learning